Evaluation of the Predictive Validity of a Risk-Need-Responsivity Assessment Tool (RNR-A) in the Swedish Prison and Probation Service - Bäckström, Peter Johansson (The prison journal, 2022)
To appraise the “real-world” implementation of the risk principle, this study examined the predictive validity of a Risk-Need-Responsivity assessment in the Swedish Prison and Probation Service. Reconviction rates at 24 months follow-up in a cohort of 2,442 offenders were used to assess calibration and discrimination indices. Results indicated acceptable predictive accuracy (AUC = .68–.74), with scope for improvement among young adult offenders. The tool's utility was supported foremost by its ability to screen out low-risk offenders, while over-prediction of recidivism among medium- and high-risk offenders calls for more comprehensive assessment to inform the effective planning of rehabilitative service intensity.